Cu-catalyzed multicomponent reaction of arylhydrazines with β-ketoesters and TBN: one-pot access to N 2-aryl 1,2,3-triazole-1-oxides - Mujahid, Mohammad; Vara, Vijay; Arshad, Usman; Gamidi, Rama Krishna; Muthukrishnan, M. (Journal of Organic Chemistry, 2024)
We report a copper-catalyzed one-pot, multicomponent strategy for the convenient synthesis of N 2-aryl 1,2,3-triazole-1-oxides using arylhydrazines, beta-ketoesters, and tert-butyl nitrite. This mild and simple reaction proceeds in an atom-economic manner with broad substrate scope, affording a variety of N 2-aryl 1,2,3-triazole-1-oxide derivatives. Other salient features of the reaction are good functional group tolerance, scalability, and product diversification.